2014
DOI: 10.1016/j.smr.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Branding athletes: Exploration and conceptualization of athlete brand image

Abstract: 2016-12-23T18:49:38

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
316
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(347 citation statements)
references
References 40 publications
16
316
0
15
Order By: Relevance
“…According to this definition, all individual athletes can be considered as brands because every athlete holds a unique name, distinctive appearance, and a personality (Arai, Ko, & Ross, 2014). As personal brands differ from brands for products or services, athletes also discussed in the context of human brands (Arai, Ko, & Kaplanidou, 2013;Arai et al, 2014;Hasaan, Kerem, Biscaia, & Agyemang, 2016). Unlike products or services, human beings act on multiple motives.…”
Section: Athlete Brandmentioning
confidence: 99%
See 3 more Smart Citations
“…According to this definition, all individual athletes can be considered as brands because every athlete holds a unique name, distinctive appearance, and a personality (Arai, Ko, & Ross, 2014). As personal brands differ from brands for products or services, athletes also discussed in the context of human brands (Arai, Ko, & Kaplanidou, 2013;Arai et al, 2014;Hasaan, Kerem, Biscaia, & Agyemang, 2016). Unlike products or services, human beings act on multiple motives.…”
Section: Athlete Brandmentioning
confidence: 99%
“…Therefore, an athlete brand is an example of a branded person or human brand like other celebrity brands. As with other celebrity brands, an athlete brand is related to the personality and image of a particular athlete as perceived by the public (Arai et al, 2014;Cortsen, 2013). Arai et al (2014) explain that an athlete brand is related to the personality of the athlete.…”
Section: Athlete Brandmentioning
confidence: 99%
See 2 more Smart Citations
“…Keller's CBBE proposed attitudinal based dimensions to measure 5 Running head: COMMUNICATING THE ATHLETE AS A BRAND brand equity, and suggested that consumer based brand equity is derived from the effect of brand knowledge (e.g., brand awareness and brand association) on consumers' reaction to the marketing and communication of the brand. Utilizing CBBE as its theoretical framework, Arai et al (2014) proposed a conceptual Model of Athlete Brand Image (MABI). The MABI is comprised of three brand association dimensions for athletes: athletic performance, attractive appearance, and marketable lifestyle.…”
Section: Literature Reviewmentioning
confidence: 99%